Poder cultural: mecanismos de consolidação do poder na arte e no entretenimento no século 21 - Ballerini, Franthiesco (2022)
This thesis, presented in the Post-Graduation Program in Social Communication (Poscom) of Universidade Metodista de São Paulo (Umesp), aims to comprehend the mechanisms of achievement and consolidation of cultural power in the 21st century. Cultural power is manifested within the fields of arts and entertainment, which products are the focus of the coverage and critical reflection of the mass media (newspapers, magazines, television, radio etc.) and post-mass media (social media, cell phone apps etc.). Cultural power is constituted under the individual and systemic faces. In the individual aspect, cultural power takes as main theoretical framework the critical thoughts of Pierre Bourdieu (2011) about what he calls symbolic power and its correlation with the concepts of habitus, field, belief and distinction. In the systemic aspect, cultural power can be constituted when the individual is inserted in consolidated international systems of power, known as soft power, term coined in the 1980’s by the political scientist Joseph Nye (2004) about the ability to get something via attraction, instead of coercion and payments, which may example, in the cultural field, is Hollywood, that was able to destabilize closed regimes such as the Soviet Union. As adjacent forces for cultural power consolidation are six categories outlined here: 1-time; 2-content (subcategory: beauty); 3-context; 4-space (subcategory: idiom); 5-fame; 6-celebrity. The research proposes a quantitative comparative measure, of understanding character, of the cultural power of 10 artists in different fields: Mauricio de Sousa and Hayao Myazaki (animation/directing); Helena Solberg and Safi Faye (cinema/directing); Anitta and Dua Lipa (music/videoclip); Brad Pitt and Shah Rukh Khan (cinema/acting); Adriana Esteves and Thalía (soap opera/acting). This research has as its main goal to offer proper tools to readers, spectators, critics, students and educators in promoting a critical reading of artistic and cultural products of our time. The analysis of the theories and practices that build cultural power, in the new context of the culture and communication of the 21st century, aims to elucidate these instruments that enable a reading and deconstruction of images, words and speeches in arts and entertainment, that almost never are innocent or devoid of purpose. It seems to have no better method to comprehend cultural power in the 21st century as the essay, which had as one of its greatest advocates the German sociologist Theodor W. Adorno, who wrote, in 1954, The essay as form, one of the strongest defenses of this method within social and human sciences. This research is also part of the interdisciplinary research “From comprehension as method”, based in Poscom of Metodista (AU)